Analysis of military construction period Hetmanate in scientific and analytical memoir writings of military historians interwar twentieth - Roman Melnyk (Cхід, 2013)
In the studio solved the problem associated with the analysis of military construction period Hetman of the Ukrainian military literature of the 20-30th years of XX century. Displaying basic conceptual approaches to military researchers studying the historical experience of nation-building period of the armed forces of the Ukrainian State of Hetman Pavlo Skoropadsky.